Predictors of acute kidney injury in patients after extracorporeal cardiopulmonary resuscitation. (March 2023) - Gaisendrees, Christopher; Ivanov, Borko; Gerfer, Stephen; Sabashnikov, Anton; Eghbalzadeh, Kaveh; Schlachtenberger, Georg; Avgeridou, Soi; Rustenbach, Christian; Merkle, Julia; Adler, Christopher; Kuhn, Elmar; Mader, Navid; et al.
Objectives: Extracorporeal cardiopulmonary resuscitation (eCPR) is increasingly used due to its beneficial outcomes and results compared with conventional CPR. Data after eCPR for acute kidney injury (AKI) are lacking. We sought to investigate factors predicting AKI in patients who underwent eCPR. Methods: From January 2016 until December 2020, patients who underwent eCPR at our institution were retrospectively analyzed and divided into two groups: patients who developed AKI ( n  = 60) and patients who did not develop AKI ( n  = 35) and analyzed for outcome parameters. Results: Overall, 63% of patients suffered AKI after eCPR and 45% of patients who developed AKI needed subsequent dialysis. Patients who developed AKI showed higher values of creatinine (1.1 mg/dL vs 1.5 mg/dL, p ⩽ 0.01), urea (34 mg/dL vs 42 mg/dL, p = 0.04), CK (creatine kinase) (923 U/L vs 1707 U/L, p = 0.07) on admission, and CK after 24 hours of ECMO support (1705 U/L vs 4430 U/L, p = 0.01). ECMO explantation was significantly more often performed in patients who suffered AKI (24% vs 48%, p = 0.01). In-hospital mortality (86% vs 70%; p = 0.07) did not differ significantly. Conclusion: Patients after eCPR are at high risk for AKI, comparable to those after conventional CPR. Baseline urea levels predict the development of AKI during the hospital stay.